2020
DOI: 10.1016/j.waojou.2020.100487
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of a glutaraldehyde-modified, L-tyrosine-adsorbed and monophosphoryl lipid A-Adjuvanted allergen immunotherapy in patients with allergic asthma sensitized to olive pollen: A retrospective, controlled real-world study

Abstract: Background Allergy to olive pollen is one of the primary causes of allergic asthma in Spain. Even though allergen immunotherapy (AIT) has shown clinical benefits in patients sensitized to different allergens, studies in asthmatic patients sensitized to olive pollen are insufficient. Objective To assess the effectiveness and safety of an ultra-short course of AIT with an L-tyrosine-adsorbed and monophosphoryl lipid A-adjuvanted olive pollen and olive/grass pollen extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…However, adjuvants can cause inflammation at the administration site 193 . Innovative adjuvants include microbial products such as TLR4‐ligand monophosphoryl lipid A (MPLA) that is safe and effective in treating asthma in patients sensitized to olive pollen, 194 flaggelin, that enhances immunogenicity and reduces allergenicity for birch AIT, 195 or CpG which has in some studies been shown to be effective in the treatment of allergic rhinitis 196 . Other potential candidates include virus‐like particles (VLPs), enhancing immunomodulation during AIT 197 .…”
Section: Advances In Ait Compound Technologymentioning
confidence: 99%
“…However, adjuvants can cause inflammation at the administration site 193 . Innovative adjuvants include microbial products such as TLR4‐ligand monophosphoryl lipid A (MPLA) that is safe and effective in treating asthma in patients sensitized to olive pollen, 194 flaggelin, that enhances immunogenicity and reduces allergenicity for birch AIT, 195 or CpG which has in some studies been shown to be effective in the treatment of allergic rhinitis 196 . Other potential candidates include virus‐like particles (VLPs), enhancing immunomodulation during AIT 197 .…”
Section: Advances In Ait Compound Technologymentioning
confidence: 99%
“…The percentage of patients discontinuing inhaled corticosteroids (ICS) was 50% vs. 5% at the second year and 63% vs. 9.3% at the third season. Florido et al in a retrospective way assessed 131 patients (89 SCIT and 42 matched patients) receiving olive allergoid SCIT [30]. Unscheduled visits and emergency room admissions were evaluated and it was found a significant reduction (about one half) in these two considered parameters in the SCIT group vs. the controls, plus a reduction in the ICS intake, whereas no change was seen in medications for rhinitis.…”
Section: Key Pointsmentioning
confidence: 99%